Switching to coformulated rilpivirine (RPV), emtricitabine (FTC) and tenofovir alafenamide from either RPV, FTC and tenofovir disoproxil fumarate (TDF) or efavirenz, FTC and TDF: 96‐week results from two randomized clinical trials1. Issue 10 (12th August 2018) - Hagins, D; Orkin, C; Daar, ES; Mills, A; Brinson, C; DeJesus, E; Post, FA; Morales‐Ramirez, J; Thompson, M; Osiyemi, O; Rashbaum, B; Stellbrink, H‐J; et al.
Abstract : Objectives: The single‐tablet regimen rilpivirine, emtricitabine and tenofovir alafenamide (RPV/FTC/TAF) for treatment of HIV‐1‐infected adults was approved based on bioequivalence. We assessed the clinical efficacy, safety and tolerability of switching to RPV/FTC/TAF from either RPV/FTC/tenofovir disoproxil fumarate (TDF) or efavirenz (EFV)/FTC/TDF. Methods: We conducted two distinct randomized, double‐blind, active‐controlled, noninferiority trials in participants taking RPV/FTC/TDF (Study 1216) and EFV/FTC/TDF (Study 1160). Each study randomized virologically suppressed (HIV‐1 RNA < 50 copies/mL) adults (1:1) to switch to RPV/FTC/TAF or continue their current regimen for 96 weeks. We evaluated efficacy as the proportion with HIV‐1 RNA < 50 copies/mL using the Food and Drug Administration snapshot algorithm and prespecified bone and renal endpoints at week 96. Results: We randomized and treated 630 participants in Study 1216 (RPV/FTC/TAF, n  = 316; RPV/FTC/TDF, n  = 314) and 875 in Study 1160 (RPV/FTC/TAF, n  = 438; EFV/FTC/TDF, n  = 437). In both studies, the efficacy of switching to RPV/FTC/TAF was noninferior to that of continuing baseline therapy at week 96, with respective percentages of patients with HIV RNA < 50 copies/mL being 89.2% versus 88.5% in Study 1216 [difference 0.7%; 95% confidence interval (CI) −4.3 to +5.8%] and 85.2% versus 85.1% in Study 1160 (difference 0%; 95% CI −4.8 to +4.8%). No participant on RPV/FTC/TAF developed treatment‐emergent resistance versus two on EFV/FTC/TDF and one on RPV/FTC/TDF. Compared with continuing baseline therapy, significant improvements in bone mineral density and renal tubular markers were observed in the RPV/FTC/TAF groups ( P  < 0.001). Conclusions: Switching to RPV/FTC/TAF from RPV/FTC/TDF or EFV/FTC/TDF was safe and effective and improved bone mineral density and renal biomarkers up to 96 weeks with no cases of treatment‐emergent resistance.